Analisis Efektivitas Biaya Penggunaan Antibiotik terhadap Pasien Sepsis Pediatrik di Rawat Inap RSD dr. Soebandi Kabupaten Jember pada Tahun 2014 (Cost effectiveness Analysis of Antibiotics in Hospitelized Pediatric Sepsis Patients at RSD dr. Soebandi Je - Nurul Faridah; Afifah Machlaurin; Prihwanto Budi Subagio (UPT Percetakan dan Penerbitan Universitas Jember, 2016)
Antibiotics play an importent role in sepsis therapy. Inappropiate antibiotic theraphy leads to resistance of antibiotic resulting increase length of stay (LOS), mortality, and higher cost. The purpose of this study was to determine the most effective empirical antibiotic based on cost effectiveness analysis (CEA) in pediatric patients with sepsis at RSD dr. Soebandi in 2014. This study observed medical and payment records retrospectively. From 152 patient analyzed, 51 patients included and 136 patients were excluded because of the antibiotic theraphy less than three days, the age more than 18 years old and the data was not complete. The effectiveness parameter of this study were length of stay (LOS), length of stay antibiotic related (LOSAR) and 28-days mortality. According to this study, ampicillin sulbactam plus amikacin combination had shorter LOS (13,82 days) than other antibiotics. However monotheraphy ampicillin sulbactam had shorter LOSAR (7.13 days) and lower 28-days mortality (50.00%). The total cost and antibiotic cost analysis showed that ampicillin sulbactam plus amikacin combination was cheaper than other antibiotics (Rp 5,130,000.00 ± 500.00). Based on CEA and quadrant analysis ampicilin sulbactam combination plus amikacin was the most cost effective with low cost and high effectiveness (quadrant II) than other antibiotic. Keywords: cost effectiveness, antibiotic, sepsis